A Study on the Factors Affecting Depression of the Disabled People in Korea (Medico Legal Update, 2020)
Background/Objectives: The purpose of research is to construct a living environment and provide appropriate welfare resources to reduce the depression by identifying the factors affecting the depression of the disabled people.Method/Statistical Analysis: This research analyzed the data of 2017 which is the 12th data of the Korea Welfare Panel conducted by the Korea Institute for Health and Social Affairs. In order to identify the factors affecting the depression of the disabled, this research analyzed the difference of depression according to demographic factors. In addition, the factors affecting depression were surveyed through the regression analysis of the SPSS statistics program.Findings: The high scores of people with disabilities on depression indicate that access to mental health is essential in the areas of disability support, which suggests that life cycle management should be carried out through all subjects regardless of their socio-demographic variables. The result of a hierarchical regression analysis through demographic variables, satisfaction, and social support variable is as follows. First, in the area of demographic variables, male more than female, the lower is household income and the higher is one’s work ability, depression turned out to be high. Next, the result of analysis showed significant results in all variables excluding all ages and education level. When all variables are included, male more than female, the lower is one’s household income, the more one has work ability, depression was high, and the lower is one’s health satisfaction, residential satisfaction, family life satisfaction, and social support, depression turned out to be low, suggesting that individual, family, and social resource environment are important explanatory factors in the perception of depression for the disabled.Improvements/Applications: It is clear that, as a method to reduce depression of the disabled, a comprehensive and environmental approach is necessary which encompasses familial, psychological, and social dimensions